Forecasting the impact of financial decentralization in the formation of the budget of Poltava region on the basis of adaptive models (Economics and region, 2021)
The decentralization reform that is actively developing in Ukraine requires new approaches to the formation of regional economic policy. The development of Ukraine as a democratic, independent country requires improving the quality of public administration, the formation of effective socio-economic policy. The vector of reform changes in the economic system of the region is financial decentralization, which is based on the social needs of united territorial communities. Financial decentralization is one of the important conditions for the independence of local authorities and serves to effectively ensure the provision of public services based on the necessary local needs. The scientific article examines the impact of budget decentralization on the budget of Poltava region. The statistics of revenues and expenditures in the period before the reform and after its implementation are analyzed. On the basis of empirical data with the help of adaptive models the forecast values of local budget revenues for the future period are calculated, the percentage of accuracy and quality of the forecast is determined. The disadvantages of using models of general use are determined on the basis and methods of their improvement by adaptation of correlation coefficients to factors of the Ukrainian economy are offered. Prospects for the development of reform in Ukraine have been identified.
Keywords: decentralization; budget; revenues; reform; adaptive model; forecast